Analisis Pengaruh Metode Penyayatan dan Laju Pengumpanan terhadap Akurasi Dimensi dan Kekasaran Permukaan Kayu Olahan High Moisture Resistant - Muhammad Fahrudin; Imam Syafa’at; Muhammad Abdul Wahid; Agung Ari Purwanto; Bahtiar Rahmat; Wahyu Widiyanto (Jurnal Rekayasa Mesin, 2026)
The Indonesian furniture industry holds significant potential in the global market, contributing 1.16% to GDP in the first quarter of 2024. This study aims to analyze the effects of cutting methods and feed rates in CNC milling on dimensional accuracy and surface roughness of High Moisture Resistant (HMR) engineered wood. The experiment was conducted using a Completely Randomized Design (CRD) with statistical analysis through Analysis of Variance (ANOVA). Treatments included conventional and climb cutting methods, as well as feed rates of 33 mm/s and 66 mm/s, applied to specimens measuring 50 mm × 35 mm × 18 mm with a cutting depth of 4 mm. Results indicate that cutting methods significantly affected specimen length, width, and surface roughness (P-value < 0.05; F > F critical). However, microstructural observations revealed that cutting methods did not significantly influence surface roughness. Feed rate showed no significant effect on specimen length or surface roughness (P-value > 0.05; F < F critical), but significantly affected specimen width (P-value < 0.05; F > F critical). Conversely, microstructural analysis demonstrated that feed rate influenced surface roughness. Overall, cutting method was identified as the dominant factor affecting dimensional accuracy and surface roughness of HMR, while feed rate had greater influence on specimen width and microstructural surface conditions.